Fecal Microbiota Transplantation Ameliorates Experimentally Induced Colitis in Mice by Upregulating AhR - Wei, Yan-Ling; Chen, Yu-Qin; Gong, Hao; Li, Ning; Wu, Kang-Qi; Hu, Wang; Wang, Bin; Liu, Kai-Jun; Wen, Liang-Zhi; Xiao, Xiao; Chen, Dong-Feng (Frontiers in Microbiology, 2018)
Ulcerative colitis is a worldwide epidemic, chronic and nonspecific inflammatory bowel disease. Fecal microbiota Transplantation(FMT) as a new method has been used in clinical treatment for UC, however the molecular mechanisms behind this effect have yet to be fully understood. Animal models provide the means to test whether FMT promote the recovery of colon inflammation Administration of 2 % Dextra sulfate sodium(DSS) for 7 d successfully induced acute colitis associated with diarrhea, hematochezia and colon shortening, as well as a loss of body weight. FMT alleviated the severity of colon mucosa injury and improved histological alterations compared with the DSS group. In addition, FMT can promoted homeostasis of the gut microbioata. Furthermore, FMT up-regulated the expression of aryl hydrocarbon receptor(AHR), IL-10 and TGF-β in colon tissues. These results suggest that the significant anti-inflammatory effect of FMT may be attribute to its promotion of IL-10 and TGF-β production and AHR activation. In view of these results, FMT had a favorable therapeutic effect on DSS- induced ulcerative colitis.